Winnie the Pooh - Hall, Don.; Anderson, Stephen (Stephen J.); Del Vecho, Peter; Spencer, Clark; Cleese, John.; Ferguson, Craig, 1962-; Cummings, Jim, 1952-; Luckey, Bud, 1934-; Boulter, Jack.; Oates, Travis; Anderson-Lopez, Kristen; Hall, Wyatt Dean.; et al. (Burbank, Calif. : Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2011)
"When sad old Eeyore loses his tail, Owl sends the whole gang--Pooh, Tigger, Rabbit, Piglet, Kanga and Roo--on a wild journey to help Eeyore and save Christopher Robin from the mysterious Backson"--Container. In the end, it turns out to be a very busy day for a bear who simply set out to find some 'hunny.'
Originally released as a motion picture in 2011.
Based on the "Winnie the Pooh" works by A.A. Milne and E.H. Shepard.
Original songs, Kristen Anderson-Lopez, Robert Lopez ; music, Henry Jackman ; editor, Lisa Linder SIlver.
Voices: John Cleese, Jim Cummings, Bud Luckey, Craig Ferguson, Jack Boulter, Travis Oates, Kristen Anderson- Lopez, Wyatt Dean Hall, Tom Kenny, Huell Howser.
MPAA rating: G; bonus material not rated.
DVD, region 1, NTSC; Dolby Digital 5.1.
Keywords: Friendship -- Drama; Winnie-the-Pooh (Fictitious character) -- Drama; Eeyore (Fictitious character) -- Drama; Tigger (Fictitious character) -- Drama; Children's films; Feature films; Animated films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities